Using Innovative Pedagogies in the Classroom: Re-Storying Gothic Tales as Entrepreneur Stories. (October 2015) - Cardow, Andrew; Smith, Robert
It can be difficult to interest students in academic topics if they have no prior exposure to or experience of the subject. The authors introduce and discuss a pedagogic innovation designed to trigger interest in entrepreneurship and 'enterprise culture'. They use fiction in the form of Gothic context and the vampire motif to move the student through Bloom's cognitive levels of learning. The vampire is a mythic creature spawned from the deepest recesses of folkloric imagination. The entrepreneur might be seen in a similar light. The authors therefore explore these 'Byronic heroes' and vampirism as heuristic devices to help re-story and better understand entrepreneurial processes and narratives. They demonstrate that there are elements of enterprise discourse in contemporary narratives and images of vampires. The analysis is based on observations of the late 1990s early 2000s teenage television serial 'Buffy the Vampire Slayer', which retains its popular and academic cult status. Through the identification of the familiar (vampires and Buffy) as examples of the entrepreneurial construct, the unfamiliar (the construct of entrepreneurship) is made more accessible because both students and faculty approach it from a shared understanding rather than from a position of inequality. Themes of morphology and transformation emerge, but the paper's main contribution lies in its account of a novel way of teaching entrepreneurship to a new generation of students. It offers insights into making entrepreneurship more interesting for students and so into developing an entrepreneurial mindset. At the same time, the process allows for discussion of how the student has become aware of the concepts of entrepreneurship, thus facilitating knowledge in a non-threatening way.